IMPLEMENTASI METODE DETEKSI TEPI CANNY PADA OBJEK SEBAGAI MODEL KEAMANAN APLIKASI PADA SMARTPHONE ANDROID: Abdul Haris, Andi Prasetyo - Jurnal, Redaksi Tim (PETIR, 2019)
The development of technology push security system applications on android smartphone to develop one of its features that is detection of the object. The detection of Objects is a technology that allows us to identify or verify an object through a digital image by matching the texture of the object with the curve of the data objects stored in the database. For example, to match the curve of the face such as the nose, eyes and chin. There are several methods to support the work of object detection among which edge detection. Edge detection can represent the objects contained in the image of the shape and size as well as information about the texture of an object. the best method of edge detection is canny edge detection which has the minimum error rate compared with other edge detection methods. Canny edge detection will generate the image that has been processed into a new image. The new image will be stored on a database that will be matched to the image of a new object that is used as the opening applications on android smartphone.